Hinter_Fragen der Erziehungswissenschaft Perspektiven auf Pädagogik, Wissenschaft und Gesellschaft - Korneli, Karina; Bartels, Bente Henrike; Biehler, Lukas; Bringmann, Barbara Marie-Christin; Bruhnke, Lorena; Dobmeier, Florian; Kamenik, Anna Maria; Rose, Alexander; Wiese, Hannah (SKEW - Studierendenkongress Erziehungswissenschaft, 2023)
The book follows the II. Student Congress on Educational Science (SKEW), which took place at Bielefeld University in September 2021.From subjectivity and gender, emotionality and epistemology to science communication, school revolution, participation and critical educational theory: the authors address topics of digitalization and globalization processes from an educational perspective, revealing new perspectives on the self-understanding of educational science.